Membangun Kemandirian Remaja: Kunci Sukses dalam Karir - Pradita Ataza; Ronadia Ronadia; M. Andreansyah; Sani Safitri; Syarifuddin Syarifuddin (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
Independence is a fundamental element that develops alongside the changes occurring within an individual, influenced by personal needs, societal demands, advancements in knowledge, and differing life goals. Various factors affect the changes in adolescent independence, starting from external pressures or the individual’s desire to become more independent and less reliant on others. This article discusses the definition of adolescent independence, the factors influencing it, the relationship between adolescent independence and career success, as well as theories and strategies for developing adolescent independence. The aim of this article is to encourage positive changes in the independence of teenagers who wish to start living independently in the world.